The role of volumetric power input in the growth, morphology, and production of a recombinant glycoprotein by Streptomyces lividans in shake flasks (2014)
The impact of flask geometry on Streptomyces lividans growth and morphology, production and Omannosylation of a recombinant O-glycoprotein (APA from Mycobacterium tuberculosis) was described and associated to the evolution of the volumetric power input (P/V) in three shake flask geometries -- During the exponential growth, the highest P/V was found in baffled flasks (BF) with 0.51 kW/m3, followed by coiled flasks (CF) with 0.44 kW/m3 and normal Erlenmeyer flasks (NF) with 0.20 kW/m3 (flasks volume of 250 mL, filling with 50 mL and agitated at 150 rpm) -- During the stationary phase, P/V decreased 20% in BF and CF, but increased two times in NF, surely due to changes in mycelial morphology and its effects on rheology -- Also, NF cultures were carried out at a filling volume and agitation of 15 mL, 150 rpm (15 mL-NF), and 25 mL, 168 rpm (25 mL-NF), in order to raise P/V closely to the values obtained in CF -- However, different growth, morphology and recombinant protein productivity were obtained -- These data indicate that P/V is not a definitive parameter that can determine bacteria growth and morphology, not even glycoprotein production -- But it can be proposed that the oxygen transfer in the center of the pellets and hydromechanical stress might be the more relevant parameters than P/V